An acute care collaboration vanguard: translating a perioperative service from a tertiary referral centre to a district general hospital (DGH). (2019) - Casas, Ruth De Las; Whittle, Anna; Meilak, Catherine; Partridge, Judith; Dhesi, Jugdeep
No abstract available